Effect of background magnetic field on the electron-bunching and saturation phenomenon in a gyro-TWT - Singh R.K. (My University, 2025)
A self-consistent nonlinear simulation model has been presented to analyze the nonlinear behaviour of a gyro-TWT amplifier. It employs a slow-time scale formulation such that the numerical calculation time and the number of numerical integration steps have been drastically reduced. Beam-wave interaction mechanism has been presented with the help of electron flight diagram. The effect of variation of the static magnetic field on the bunching of the electrons along axial direction has also been clearly presented. The electron flight diagram thus obtained clearly demonstrates the electron defocusing and its effect on the saturation behaviour of the device. © 2012 IOS Press and the authors. All rights reserved.